Analysis of Market Orientation and Innovation Capabilities in Increasing Competitive Advantage (Survey on MSMEs Fashion in Cibadak Market, Sukabumi) - Anjalina Nurwahyuni Fazlilah; R. Deni Muhammad Danial; Resa Nurmala (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Cibadak Market is a growing center of economic activity, where fashion MSME players face challenges in meeting consumer needs and keeping up with changing fashion trends. Low understanding of market preferences as well as limited innovation and product differentiation has led to decreased competitiveness and customer loyalty. This study aims to determine the effect of market orientation and innovation capability on competitive advantage in fashion MSMEs in Cibadak Market, Sukabumi. This study uses a quantitative approach with an associative descriptive method. The population in this study were all fashion MSME players in Cibadak Market, with a sample size of 32 respondents determined through saturated sampling technique. The results showed that market orientation has a positive and significant effect on competitive advantage. In addition, innovation capability also has a positive and significant influence on competitive advantage. The implementation of good market orientation and high innovation capability can increase the competitiveness of fashion MSMEs in the local market.